METHODS FOR EFFECTIVE ORGANIZATION OF ENGLISH LESSONS IN DISTANCE LEARNING (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article covers the methodological foundations of effective organization of English lessons in distance learning. The relevance of the study is due to the increased need for online teaching of foreign languages, especially during the pandemic. The article presents the results of a study conducted using analysis, observation, questionnaire and experimental methods. According to the results, it was found that lessons using interactive tools are more effective than traditional methods. The author gives scientific and practical recommendations for organizing lessons in distance learning based on interactive, motivational and technological approaches.